Diachrony, Synchrony, and Typology of Tense and Aspect in Old Japanese - Watanabe, Kazuha (Lexington Books, 2021)
This book reconstructs the synchronic system of tense and aspect in Old Japanese. Watanabe takes a fundamentally different approach from previous analyses by examining the syntactic distribution of temporal suffixes in Manyōshū, an eighth-century poetry collection.